Secagem de gel ágar - Moreira, Marcos Flávio Pinto (Universidade Federal de São Carlos, 2000)
Agar-agar is a hydrofilic colloid extracted from seaweed, mainly from algae Gelidium. It s used as culture medium in microbiology and as emulsificant, stabilizer and gelling in foods. Drying is an important operation in the extractive process to obtain Agar-agar, because it defines the form, color and final moisture content of product. In order to study the drying of agar gel, equilibrium and drying experiments are needed. The equilibrium of agar-water-air was investigated using the static gravimetric method and drying experiments were performed in a forced convection dryer. To determine equilibrium moisture content values, the static method was used with saturated saline solutions where operational conditions of temperature and relative humidity ranged from 25.0°C to 50.0°C and 11.0% to 84.0%, respectively. The determination of moisture content was based on Lees method. The drying experiments were performed with temperatures from 30.0°C to 50.0°C and superficial air velocities from 1.0 to 4.0 m/s. Based on the experimental procedure above, the equilibrium of agar-water-air could be reasonable described by the G.A.B. (Guggenheim-Anderson-de Boer) model. It was verified, using Lewis equation, that temperature and velocity of air influence the drying operation. Finally, at a constant drying rate, the drying of agar gel and water are very similar. The constant drying rate of agar gel has been represented by a relationship for evaporation of water. The decreasing drying rate of agar gel was represented by the characteristic curve. All results obtained in this work serve as contribution to the process to obtain the agar, which utilizes the drying.
Keywords: Secagem; Processos de secagem e evaporação; Isotermas de equilíbrio; Cinética de secagem; Colóides; Ágar; ENGENHARIAS::ENGENHARIA QUIMICA